Clinical value of 18F-FDG-PET/CT in staging cutaneous squamous cell carcinoma. Issue 7 (July 2019) - Mahajan, Sonia; Barker, Christopher A.; Singh, Bhuvanesh; Pandit-Taskar, Neeta
Abstract : Background: Cutaneous squamous cell carcinoma (cSCC) is the second most common skin malignancy. Computed tomography (CT) and/or MRI are commonly used for staging, however, the role of fluorine-18-fluorodeoxyglucose ( 18 F-FDG)-PET is not clearly established. In this study, we evaluated 18 F-FDG-PET/CT imaging for initial staging of cSCC. Patients and methods: 18 F-FDG-PET/CT scans performed in patients with newly diagnosed cSCC were reviewed retrospectively. Images were visually assessed for lesions and 18 F-FDG uptake [standardized uptake value (SUV)] in primary and secondary sites was measured. Suspected lesions on 18 F-FDG-PET/CT were correlated with histopathology when available, follow-up imaging or clinical data in others. Results: Twenty-three cSCC patients who underwent 18 F-FDG-PET/CT at diagnosis were evaluated. Primary sites were in head/neck ( n =21), chest ( n =1), and foot ( n =1). All patients had 18 F-FDG-positive scans with a total of 51 18 F-FDG-positive lesions. All primary lesions ( n =24) were 18 F-FDG-positive (SUV: 2.3–22.8; mean 10.2), and additional 27 18 F-FDG-positive lesions, including 21 nodes, four cutaneous, one osseous and one lung lesion, were noted in 13 patients. Mean size of 18 F-FDG-positive nodes was 0.9 cm (range: 0.4–2.5 cm), predominantly clinically impalpable. Pathology was available for 40/51 lesions; 31 sites positive for malignancy. SUV (mean±SD) was 9.2±6.2 for malignant and 2.7±1.2 for benign lesions. Sensitivity, positive predictive value, and accuracy of 18 F-FDG-PET/CT scan were 100, 77.5, and 77.5%, respectively. 18 F-FDG detected seven additional lesions in three patients, compared to CT/MRI. Overall, staging 18 F-FDG-PET/CT detected nine prior unknown lesions in five patients that were proven metastatic disease by histopathology or follow-up; 18 F-FDG-PET/CT modified management in 5/23 (21.7%) patients. Conclusion: 18 F-FDG-PET/CT has high sensitivity in the detection of cSCC lesions, including small cutaneous and nodal disease, and has a potential role in initial staging and management.